Կարապետ Մելիք-Օհանջանյանի արխիվը. մահվան 50-րդ տարելիցի հիշատակին - Քեշիշյան, Մերի (Մատենադարան)
The archive of the distinguished philologist and expert in Armenian and Middle Eastern studies, academician Karapet Melik‘-Ohanjanian is kept at Matenadaran. For many years it had belonged to his daughter Lusik Melik‘-Ohanjanian. After her death in 2001, her relatives donated it to Matenadaran. Melik‘-Ohanjanyan was born in 1893 in the village Kaler of the Meghri region (in the Syunik‘ province of the RA). He studied in the boys’ school of Gandzak for two years. In 1903 he entered the Lazarev institute of Eastern Languages in Moscow. As a talented student, in 1914 he was sent to the University of Berlin to become a student in Middle Eastern Studies and philosophy. In 1920 Melik‘-Ohanjanyan returned to Armenia. He worked at the Ministry of Public Education and Art. In 1921 he was appointed the head of the first academic institution of the republic, the Etchmiadzin Institute (Matenadaran). He devoted his whole life to teaching, research and academic management. In 1935 he gained professorship, in 1962 he was conferred the title of Honored Scholar and in 1965 he was elected academician of the Armenian Academy of Sciences. In 1937–1942 Melik‘-Ohanjanyan suffered political repression, and only in 1956 he was acquitted and his civil rights were restored. He died on February 22, 1970, in Yerevan. В архиве Матенадарана хранится фонд известного арменоведа, филолога, востоковеда академика Карапета Мелик-Оганджаняна. Этот ценный архив долгие годы хранила дочь ученого Лусик Мелик-Оганджанян, а после ее смерти в 2001 году родственники передали его Матенадарану. К. Мелик-Оганджанян родился в 1893 г. в деревне Калер Мегринского района (РА, Сюникская область). Два года он учился в гандзакской мужской гимазии, в 1903 г. поступил в Московский Лазаревский институт восточных языков. В 1914 г. его как одаренного студента отправили на учебу в Берлинский университет (востоковедение и философия). В 1920 г. К. Мелик-Оганджанян вернулся в Армению. Работал в Министерстве народного образования и искусства, а в 1921 г. был назначен председателем первого научного учреждения республики – Эчмиадзинского института (Матенадаран). Всю свою жизнь он посвятил делу просвещения, педагогической, исследовательской и научно-организационной деятельности. В 1935 г. ему было присуждено звание профессора, в 1962 – заслуженного деятеля науки, а в 1965 г. он был избран академиком АН Арм. ССР.
Keywords: Պատմություն; Կենսագրություն